2005
DOI: 10.1007/s00702-005-0284-6
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of serum ghrelin levels in patients treated with clozapine

Abstract: We investigated serum ghrelin levels (SGL) in 12 patients with schizophrenia over a 10-week period after initiation of clozapine treatment. In contrast to increments of body mass indices (BMI, kg/m2) and serum leptin levels (SLL), no significant change in SGL was detected. Inverse correlations between delta SGL and delta SLL did not reach statistical significance. Linear mixed model analysis could not detect effects of age, sex, BMI, SLL and serum clozapine levels on SGL. Our results do not support a causal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 16 publications
0
24
2
Order By: Relevance
“…A prospective 10-week clozapine trial by Bromel (Bromel et al, 1998), found that leptin levels peaked early in treatment, at week 2, followed by a subsequent decrease and steady rise, though not to the peak levels seen earlier. This pattern was replicated in Monteleone's 32-week prospective clozapine study, again with the initial peak in serum leptin levels occurring at week two (Monteleone et al, 2002), and later studies (Theisen et al, 2005).…”
Section: Features Of Weight and Leptin Changes During Antipsychotic Tmentioning
confidence: 73%
See 1 more Smart Citation
“…A prospective 10-week clozapine trial by Bromel (Bromel et al, 1998), found that leptin levels peaked early in treatment, at week 2, followed by a subsequent decrease and steady rise, though not to the peak levels seen earlier. This pattern was replicated in Monteleone's 32-week prospective clozapine study, again with the initial peak in serum leptin levels occurring at week two (Monteleone et al, 2002), and later studies (Theisen et al, 2005).…”
Section: Features Of Weight and Leptin Changes During Antipsychotic Tmentioning
confidence: 73%
“…As patients gained substantial amounts of weight on clozapine and olanzapine, serum leptin also rose, but neither weight nor leptin changes were seen in patients exposed to haloperidol or in those who did not receive antipsychotic medication (Kraus et al, 1999). Numerous subsequent prospective trials of olanzapine-treated patients (Eder et al, 2001;Graham et al, 2005b;Ebenbichler et al, 2005;Murashita et al, 2005;Hosojima et al, 2006) and clozapine-treated patients (Monteleone et al, 2002;Kivircik et al, 2003;Sporn et al, 2005;Theisen et al, 2005) confirmed the association between use of these medications, weight gain, and increased serum leptin levels. For agents with less weight gain liability, such as high potency typicals (Hagg et al, 2001;Atmaca et al, 2003a;Atmaca et al, 2003c), sulpiride (Baptista et al, 2000), quetiapine (Atmaca et al, 2003c), or risperidone (Fitzgerald et al, 2003;McIntyre et al, 2003;Martin et al, 2004;Chiu et al, 2006), comparative trials noted modest weight gain and leptin changes, while olanzapine and clozapine exposed subjects experienced marked increases in adiposity, weight and serum leptin.…”
Section: Leptin Drug Effectsmentioning
confidence: 96%
“…In contrast, SGAs' leptin effects (Monteleone et al, 2002;Melkersson and Dahl, 2003;Ebenbichler et al, 2005;Murashita et al, 2005;Sporn et al, 2005;Theisen et al, 2005) seem to be entirely attributable to increased adiposity (Haupt et al, 2005;Sporn et al, 2005). In a cross-sectional study of plasma leptin and adiposity in schizophrenic patients treated with olanzapine (N ¼ 27), risperidone (N ¼ 24), or a typical antipsychotic (N ¼ 21), and in 124 healthy controls, BMI correlated with leptin levels in the entire sample.…”
Section: Putative Mechanisms Of Sgas-induced Weight Gainmentioning
confidence: 98%
“…Increases (Murashita et al, 2005;Palik et al, 2005), decreases (Togo et al, 2004), and no change (Sporn et al, 2005;Theisen et al, 2005;Himmerich et al, 2005) in plasma ghrelin levels were reported in patients treated with SGAs; a consensus regarding clinical significance of these changes has not yet transpired. Likewise, potential contributions to weight gain of norepinephrine (Elman et al, 2002(Elman et al, , 2004 and prolactin (Melkersson, 2005;Mann et al, 2006) increases associated with SGA treatment are still unclear.…”
Section: Putative Mechanisms Of Sgas-induced Weight Gainmentioning
confidence: 99%
“…The assertion that these problems may arise due to increases in ghrelin secretion from the stomach produced by the secondgeneration antipsychotic agents (SGAs) is however undermined by the following considerations: (a) preponderance of the studies reporting no or inverse relationship between plasma ghrelin levels and SGAs-induced weight gain (Togo et al, 2004;Palik et al, 2005;Theisen et al, 2005;Sporn et al, 2005;Hosojima et al, 2006); (b) the lack of reported evidence on ghrelin alterations in drug-free patients who are also prone for glucoregulatory abnormalities and for obesity; and (c) undetermined (primary vs secondary) mechanisms of the SGAs ghrelin effects. We have discussed the inconclusive ghrelin findings in the text (page 15) and in the tabulated format (Elman et al, 2006).…”
Section: Sirmentioning
confidence: 99%